Milling of magnesium alloy with micro cutting tools - AY, MUSTAFA (My University, 2019)
Micromachining is a method of manufacturing micro-scale products with three-dimensional and complex geometry by using engineering materials with narrow tolerances and high precision. In this study, the effects of feed, cutting speed and chip depth on milling of magnesium alloy material by micro-milling cutting tools were investigated. Taguchi method was used in the test design. By this means, time and cost were saved. The data obtained from the experiments were optimised. The effect of each parameter on the obtained results was determined by using analysis of variance (ANOVA). It is seen from the results of the experimental study obtained by the analysis of variance (ANOVA) that the most effective factor on the formation of cutting force is the revolution with 73,83%. In this study where the Taguchi method was used, the cutting force was minimized. The performance was increased, and the quality of the end product was improved. In this study, it was tried to determine the optimal workability of magnesium material with micro microfinger milling machining
Keywords: ANOVA; Magnesium; Micro-milling; Regression Analysis; Taguchi